Anti-inflammatory activity of 9-hydroxycanthin-6-one extracted from hairy-root cultures of Eurycoma longifolia potentially via aryl hydrocarbon receptor induction - Tran, Minh Duc; Tran, Trang; Nguyen, Ngan; Chu, Ha; Nakahama, Taisuke; Nguyen, Nam (Bangladesh Journal of Pharmacology, 2022)
No abstract